THE INFLUENCE OF SERVICE QUALITY AND PRODUCT QUALITY ON REPURCHASE INTENTION AT KOPI KENANGAN MANADO TOWN SQUARE - Fairus Akbar Ali Mokoginta (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
This is a quantitative study, which aims to understand, analyze and prove the influences of service quality and product quality on repurchase intention. This study uses people who have bought Kopi Kenangan as the research population. We use 100 respondents as samples in this study. In this study, we used non-probability sampling method and purposive sampling technique. The data we used in this study are collected with questionaries distribution. The data analysis in this study are multiple regression analysis methods processed with SPSS 20 program. The results of the study shows that both service quality and product quality has influences on customers’ repurchase intention.